Uneasy military encounters the imperial politics of counterinsurgency in Southern Thailand - Streicher, Ruth 1982- (Southeast Asia Program Publicatios, an Imprint of Cornell University Press, 2020)
"Analyzes how the practices of counterinsurgency applied by the Thai military in the southernmost provinces constitute Thailand as an imperial formation that rests on producing its Malay-Muslim minority as different in terms of race, gender and religion"--